Razmerje med aktivnostjo simpatika in parasimpatika pri testu z nagibno mizo - Rotar, Melita (Medicinski razgledi, 2003)
Introduction: Neurocardiogenic syncope is the most frequent transitional formof loss of consciousness, which is caused by inappropriate triggering of the Bezold-Jarisch reflex. Most commonly, the triggering agent is an upright posture. With the help of spectral analysis, researchers have demonstrated that there is a large increase in sympathetic activity just before"syncope, while at the moment of syncope a paradox inhibition of this activity occurs with consequential vasodilatation and bradycardia, which result in loss of consciousness. The objective of our study was to discover whether there are differences in autonomic nervous system activity between patients and control subjects in their responses to head-up tilt table testing and whether these differences are greater in a tilt table test with nitroglycerine. Subjects andmethods. A group of 30 subjects who received nitroglycerine during the test(NTG+) was compared with another group of 30 who were tested without nitroglycerine (NTG-). In half of the patients in each group, syncope occurredduring the test (SIN+) while in the other half it did not (SIN-). Spectral analysis of heart rate variability was used to determine the ratio ofmedium- (SF) and high-frequency (VF) bands (SF/VF), which represents the balance between the sympathetic and parasympathetic nervous systems: The results were compared using t-test for dependent samples for changes within each group, and with Student's t-test for comparison between the groups. A statistically significant difference was one with p <_ 0.05. (Abstract truncated at 2000 characters)
Keywords: Nagnjena miza, testi; Syncope, Vasovagal; Nitroglicerin; Diagnosis; Sinkopa vazovagalna; Tilt-Table Test; Elektrokardiografija; Nitroglycerin; Electrocardiography; Srčna frekvenca; Heart Rate; sinkopa; vegetativno živčevje; testi; nagib